Facing the Industrial Revolution 4.0: Taiwanese and Indonesian Perspective - Hardyanthi, Try; Al Ghozali, Falah; Wahyu, Muhammad Arizka (Universitas Muhammadiyah Yogyakarta, 2019)
Industrial Revolution 4.0 offers both challenges and opportunities for all countries. Every country has to adopt best strategies to deal with its dynamic and complexity. This paper aims at discussing the legal policies adopted by Indonesia and Taiwan to face this industrial revolution. This research employs a descriptive- qualitative method with comparative approach. It is found that Industrial Rrevolution 4.0, also known as the intelligent industry, seeks to transform a company into an intelligent organization to achieve the best business results. Indonesia officially launched the road-map called â€œMaking Indonesia 4.0â€ in 2018. In the same year, Indonesia has started to set up the main plain of the program for five focuses sectors ex: food and drink, textile and clothing, automotive, chemist and electronic, and additional ten cross priority sectors. While Taiwan proposed its own version of Industry 4.0 called â€œProductivity 4.0â€ in 2014. This includes the use of large quantity of robots and production lines, the automation of manufacturing procedures, the introduction of Industry 4.0 and Internet of Things (IoT) technology, and cloud computing for immediate data processing. It makes Industry 4.0 as the national policy for industrial transformation.